A Format-specific Bowling Performance Measure of Cricket (International Journal of Statistical Sciences, 2024)
Batting and bowling are the prime skills of cricket. Cricket literature has seen a reasonable number of measures of bowling and batting performance. But with the different formats of cricket being played at the international level currently, it is not justified to have a unified measure of performance across all formats. Any performance measure in cricket shall include the existing popular performance statistics as its building block so that the refined measures are perceivable by ordinary followers of the game. This paper attempts to develop a format-specific bowling performance measure for limited-overs cricket. The measure is a weighted multiplicative aggregation of two popular bowling statistics, viz. the bowling average and the economy rate, after range and variance equalization. The proposed measure is implemented on a sample of top 20 bowlers, as per the recent International Cricket Council (ICC) rating, for two popular limited-overs formats of cricket. The study finds that the relative importance of the bowling average and the economy rate in the bowling performance measure varied across the formats of cricket.IJSS, Vol. 24(2) (Special Issue), December, 2024, pp 181-192